Three‐dimensional intracellular transport in neuron bodies and neurites investigated by label‐free dispersion‐relation phase spectroscopy. Issue 5 (13th March 2017) - Kandel, Mikhail E.; Fernandes, Daniel; Taylor, Alison M.; Shakir, Haadi; Best‐Popescu, Catherine; Popescu, Gabriel
Abstract: Due to the limitations of fluorescence imaging techniques, the study of intracellular cargo is typically restricted to two‐dimensional analyses. To overcome low light levels and the risk of phototoxicity, we employ quantitative phase imaging, a family of full‐field imaging techniques that measure the optical path length shift introduced by the specimen. Specifically, we use spatial light interference microscopy (SLIM) to study the transport of mass in whole tomographic volumes and show that a time‐correlation technique, dispersion‐relation phase spectroscopy (DPS), can be used to simultaneously assay the horizontal and vertical traffic of mass through a cell. To validate our method, we compare the traffic inside cell bodies and neuronal extensions, showing that the vertical transport of mass may prove a more sensitive and interesting metric than similar measurements limited to a 2D, horizontal plane. © 2017 International Society for Advancement of Cytometry